Idiopathic unilateral hyperhidrosis with Holmes-Adie syndrome: Case report - Coskun, Basak Kandi; Saral, Yunus; Belirgen, Sait; Öztürk, Perihan (Japanese Dermatological Association, 2004)
Hyperhidrosis is a disease that is characterized by excessive sweating due to hyperactivation of eccrine sweat glands. It may be localized or generalized form. Holmes-Adie syndrome is an idiopathic disease with unilateral pupil dilatation and loss of deep tendon reflexes. We present a 37-year-old female patient diagnosed with unilateral hyperhidrosis co-incident with Holmes-Adie syndrome because of this unusual presentation.
Keywords: Holmes-Adie syndrome; Idiopathic unilateral hyperhidrosis